1989
DOI: 10.1042/cs0770567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endothelin on Systemic and Renal Haemodynamics and Neuroendocrine Hormones in Conscious Dogs

Abstract: 1. The effects of endothelin on systemic and renal haemodynamics and plasma concentrations of neuroendocrine hormones including plasma renin activity, aldosterone, adrenocorticotropic hormone, cortisol, catecholamines and arginine vasopressin were investigated in 18 conscious dogs. 2. Bolus injection of 4 pmol of endothelin/kg did not cause any significant changes in haemodynamics. Mean arterial pressure was elevated by both doses of 40 pmol/kg [91 +/- 2 to 99 +/- 2 mmHg (12.1 +/- 0.3 to 13.2 +/- 0.3 kPa), P l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 21 publications
1
13
1
Order By: Relevance
“…While it has previously been shown that ET-1 is able to cause the acute stimulation of ACTH release in the dog [10], in the present studies no stimulation of the release of the major ACTH-releasing hormone CRH was seen. In the peripheral vascular system, ET-1 may lead to the stim ulation of NO synthesis, which in turn may counteract at least in part some of the effects of ET-1 on the vascula ture; this effect is thought to occur mainly via the E T b receptor subtype [19], As NO has been shown to inhibit the stimulated release of CRH [27], we were concerned that the lack of effect of ET-1 might be due to the cosyn thesis of NO; however, even in the presence of the potent NO synthesis inhibitor, T-NO-Arg, no stimulation of CRH release was seen, suggesting that NO production was not masking any stimulatory effect of ET-1.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…While it has previously been shown that ET-1 is able to cause the acute stimulation of ACTH release in the dog [10], in the present studies no stimulation of the release of the major ACTH-releasing hormone CRH was seen. In the peripheral vascular system, ET-1 may lead to the stim ulation of NO synthesis, which in turn may counteract at least in part some of the effects of ET-1 on the vascula ture; this effect is thought to occur mainly via the E T b receptor subtype [19], As NO has been shown to inhibit the stimulated release of CRH [27], we were concerned that the lack of effect of ET-1 might be due to the cosyn thesis of NO; however, even in the presence of the potent NO synthesis inhibitor, T-NO-Arg, no stimulation of CRH release was seen, suggesting that NO production was not masking any stimulatory effect of ET-1.…”
Section: Discussioncontrasting
confidence: 51%
“…However, all three endothelins and their receptors have also been identified in the central ner vous system [3] with the highest levels of endothelin mRNA in hypothalamic neurons [4], suggesting that they may function as central neuromodulators [1,5,6]. Yoshizawa et al [7] originally demonstrated the pres ence of ET-1 in the endocrine hypothalamus, particularly the paraventricular and supra-optic nuclei and the poste rior pituitary; furthermore, ET-1 immunoreactivity was depleted in parallel with vasopressin in response to an osmotic stimulus, suggesting that it may be concerned in the regulation of vasopressin release [7], More direct evi dence for this control was provided by the observation that ET-1 stimulated vasopressin release from the perifused rat hypothalamus [8] or posterior pituitary [9] in vitro, while in vivo peripheral infusion of ET-1 led to a parallel increase in both vasopressin and adrenocorticotropin (ACTH) in the dog [10]. In addition, circulating levels of ET-1 and vasopressin appear to correlate in the human under different pathophysiological states [11], Specific endothelin-binding sites have been demonstrated in the central nervous system, particularly the cortex and cerebellum but also the hypothalamus [12], thus further confirming the suggested role of endothelins in the regula tion of neuro-endocrine function.…”
mentioning
confidence: 99%
“…Intravenous injection of ET decreases renal blood flow and glomerular filtration rate and increases PRA and the level of plasma AVP, ALD, and ANP in animals (27)(28)(29)(30), whereas a low dose of ET produces diuretic and natriuretic effects (31). Because the level of plasma ET did not change during PEEP in our study, ET, at least in the systemic circulation, probably does not play a role in the renal effect of PEEP.…”
Section: Anesth Analgmentioning
confidence: 99%
“…Department of Internal Medicine, School of Medicine, Keio University, Tokyo, Japan Material and Methods Surgery and animal preparation Fourteen male mongrel dogs weighing between 12 and 18 kg were used in these experiments. Under pentobarbital anesthesia, catheters (Tygon, Akron, OH) were placed in the right iliac artery and vein as previously described (18,19). The catheters were inserted sc, externalized through the back between the scapula and secured.…”
mentioning
confidence: 99%